Pelatihan Penyusunan Panduan Praktikum Materi IPA Bagi Guru IPA SMPN 2 Oelpuah Kupang Tengah - Aloysius Djalo; Hildegardis Missa; Sardina Ndukang; Aldonius Ari Gare; Gabriel Sawu; Meriana Naibaha (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The purpose of this PkM activity is to assist science teachers in developing learning tools that are oriented towards class discussion learning models by learning think pair share, buzz group, and beach ball strategies that are adapted to natural science material, namely Vitamin Testing, and Photosynthesis Experiments, which will demonstrated to students accompanied by a science teacher, and shared knowledge and experience with science teachers in preparing science learning tools with learning models and strategies adapted to the characteristics of science material. This activity was carried out at SMPN 2 Oelpuah Kupang Tengah with stages such as meetings with partners, preparation of materials, questionnaires, as well as tools and materials used for PkM activities, presentation of materials, practice of making learning tools, testing of learning tools, practicum, evaluation and reporting.The results obtained from this PkM activity were that science teachers gained new knowledge about how to prepare learning tools with various models and strategies and the participants were very enthusiastic in participating in this activity as evidenced from the analysis of the questionnaire 100% of the participants were tipped in training and practicum activities.